FORMATION OF COMPONENTS OF PRAGMATIC COMPETENCE IN A FOREIGN LANGUAGE IN STUDENTS - Makhsudakhon Abbasovna Saidova (PEDAGOGS, 2024)
Abstract: In this article, the composition of the component of pragmatic competence, which includes elements of the component of pragmatic competence in a foreign language, was determined. Approaches to the formation of the components of pragmatic competence based on the teaching of pragmatic markers were proposed.